Silicon foliar application on nutrition and growth of Phalaenopsis and Dendrobium orchids - Mantovani, Cibele [UNESP]; Prado, Renato M. [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (Elsevier, 2018)
Foliar application of silicon can be beneficial to orchid growth, but it may also impair growth depending on the source and solution concentration. Due to the lack of information on silicon toxicity in long-term orchid nutrition, experiment with two different orchid species, Phalaenopsis Golden Peoker and Dendrobium Valentine, were performed. The plants were grown in plastic trays with dry Sphagnum in a greenhouse, being fed the nutrient solution without silicon in the first six months. After that, the plants were transplanted to individual plastic vessels (0.9 L). The treatments followed a completely randomized design with a 5 × 3 factorial consisting of five Si concentrations (control, 14.3, 28.6, 42.9 and 57.2 mmol L−1) and three sources (monosilicic acid, potassium silicate, and potassium silicate and sodium silicate mixture), with five replicates. After 18 months of Si foliar application, the Si, C, N, P, K, Ca, Mg and S levels, lignin content and biometric variables were determined for both species. The application of 27 and 16 mmol L−1 Si (potassium silicate and monosilicic acid) resulted in the highest values for the evaluated biometric parameters for Phalaenopsis and Dendrobium, respectively. The results suggest that silicon foliar application affected nutrient absorption and green color index of Phalaenopsis and Dendrobium, and the lignin content of Phalaenopsis. Application of concentrations greater than 39 and 18 mmol L−1 Si over 18 months was toxic to Phalaenopsis and Dendrobium, respectively, since the orchid dry matter decreased by 10% (critical level due to toxicity). Applying increasing concentrations of Si sources decreased the C:N:P stoichiometric ratio of orchids.
Keywords: C/Si ratio; Orchid nutrition; Orchidaceae; Si toxicity; Stoichiometry